Lower extremity kinematics of athletics curve sprinting - Alt, T.; Heinrich, K.; Funken, J.; Potthast, W. (Journal of Sports Sciences, 2015)
Curve running requires the generation of centripetal force altering the movement pattern in comparison to the straight path run. The question arises which kinematic modulations emerge while bend sprinting at high velocities. It has been suggested that during curve sprints the legs fulfil different functions. A three-dimensional motion analysis (16 high-speed cameras) was conducted to compare the segmental kinematics of the lower extremity during the stance phases of linear and curve sprints (radius: 36.5 m) of six sprinters of national competitive level. Peak joint angles substantially differed in the frontal and transversal plane whereas sagittal plane kinematics remained unchanged. During the prolonged left stance phase (left: 107.5 ms, right: 95.7 ms, straight: 104.4 ms) the maximum values of ankle eversion (left: 12.7°, right: 2.6°, straight: 6.6°), hip adduction (left: 13.8°, right: 5.5°, straight: 8.8°) and hip external rotation (left: 21.6°, right: 12.9°, straight: 16.7°) were significantly higher. The inside leg seemed to stabilise the movement in the frontal plane (eversion-adduction strategy) whereas the outside leg provided and controlled the motion in the horizontal plane (rotation strategy). These results extend the principal understanding of the effects of curve sprinting on lower extremity kinematics. This helps to increase the understanding of nonlinear human bipedal locomotion, which in turn might lead to improvements in athletic performance and injury prevention.